2013
DOI: 10.1590/s2317-17822013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Escala URICA-VOZ para identificação de estágios de adesão ao tratamento de voz

Abstract: OBJETIVOS: Adaptar a escala URICA à avaliação dos estágios de mudança para a adesão de pacientes em tratamentos de voz; e verificar a relação destes com a idade do paciente, o tipo de disfonia, a escolaridade, a profissão e o número de sessões de fonoterapia. MÉTODOS: Estudo transversal, com amostra de conveniência, composta por 66 pacientes com disfonia, sendo 58 mulheres e oito homens, com idade entre 18 e 65 anos, atendidos em dois ambulatórios de instituições de ensino de Fonoaudiologia. Como instrumento e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 21 publications
1
42
0
4
Order By: Relevance
“…After considering their limitations and suggestions, the authors found most of the selected studies indicated group vocal therapy to be effective at all ages, and not only promoted vocal health, but also prevented dysphonia (3) . Unfortunately, there are few studies, in the literature, that have evaluated the patient's stage of readiness to speech therapy in the voice area (10,15,22) . Furthermore, there was no previous research into the efficacy of group therapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After considering their limitations and suggestions, the authors found most of the selected studies indicated group vocal therapy to be effective at all ages, and not only promoted vocal health, but also prevented dysphonia (3) . Unfortunately, there are few studies, in the literature, that have evaluated the patient's stage of readiness to speech therapy in the voice area (10,15,22) . Furthermore, there was no previous research into the efficacy of group therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The original version of the University of Rhode Island Change Assessment questionnaire (URICA) was designed to measure the readiness dimensions for the change in individuals who undergo to health treatments (14) and was adapted for the voice area (15) , containing 32 items. The URICA-Voice questionnaire is a self-assessment tool that is designed to assess the stage of readiness in which the patient is undergoing treatment of the voice (15) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations